Effect of Heat Treatment on Physicochemical Properties and Antioxidant Activity of Quercus acutissima - Park, Soojin (International Journal of Engineering and Technology, 2019)
This study aimed to determine changes in the physicochemical characteristics and antioxidant activity in acorn (Quercus acutissima) under different thermal treatments: A (140 Â°C), B (150 Â°C), C (160 Â°C), D (170 Â°C), and E (180 Â°C). A hot water extract (60 Â°C, 4 h) of each sample was prepared for measuring the physicochemical properties. The total phenolic and flavonoid content was determined spectrophotometrically. The pH of the heat-treated acorn was significantly lower than that of native acorn, and was inversely proportional to temperature (p < 0.05). The sugar content of acorn was significantly higher in groups heated below 160 Â°C than that of the control (p < 0.05). Total polyphenol content was the highest (0.031.59 Â± 0.21 mg GAE/mg) in the group treated at the lowest temperature (140 Â°C) (p < 0.05). Antioxidant activity depended on dose (p < 0.05), 31.03â€“95.99% and 20.49â€“99.51% for DPPH and ABTS radical scavenging activities, respectively, in heat-treated groups. The IC50 value of DPPH and ABTS in acorn was as low as 0.13 mg/mL and 0.15 mg/mL in A group, respectively. Â Thus, heat treatment of acorn significantly increased the sugar and phenolic contents and antioxidant activity at lower heat treatment temperatures. Â Â